PENERAPAN HORIZONTAL POD AUTOSCALER DAN REDIS CLUSTER BERBASIS KUBERNETES UNTUK MENINGKATKAN PERFORMA WEBSITE ELEARNING - Gurohman, Diki Taufik; Susanto, Bekti Maryuni; Hariyanto, Agus; Jullev Atmadji, Ery Setiyawan; Gumilang, Mukhamad Angga; Antika, Elly; Mukhlisoh, Nanik Anita (Universitas Budi Luhur, 2024)
Elearning is a very vital tool in learning today. To provide optimal service, elearning servers require quite large computing resources when a large number of users access them simultaneously. However, expensive computing resources such as CPU, memory and disk storage make it difficult for organizations to meet the needs of large users. Previous research compared the performance of two public clouds on a moodle-based learning management system. The results showed that backup and restore times increased by about 10 seconds for every additional 500 MB of data size. This research aims to apply Kubernetes-based horizontal pod autoscaler and Redis cluster on the Moodle elearning server. Moodle is used to run elearning and Redis as database memory which can improve website performance. Horizontal implementation of pod autoscaler and Redis cluster was able to increase the performance of the Moodle e-learning website by 4.3% compared to a monolithic approach. Research shows that implementing Kubernetes and Redis clusters can improve the performance of Moodle e-learning websites. This research also shows that the microservice approach has better performance compared to the monolithic approach..